CONCEPTUALIZING THE UNDERSTANDING OF PROFESSIONAL IDENTITY IN TEACHER’S CAREER - Ilze Mikelsone; Indra Odina; Ligita Grigule (European Scientific Journal, ESJ, 2014)
The article deals with the research designed as the Grounded Theoryto explore and conceptualize the practising teachers’ perception of their professional identity. The practising teachers – master students of the professional master study programme „Teacher” study module “Education for Well-being and Cohesion” taking the course „Educator’s Professional Identity and Pedagogic Mastery” were chosen to help to formulate the theory. Analogies (metaphors) and narrative essays have been used as the techniques for identifying concepts. Making associations, brainstorming, coding, making concepts, conceptual sorting in categories, memoing and outlining theories was the procedure how teachers conceptualized the various elements used to construct professional identity.Word frequency list and keyword- in-context list techniques were used to carry out computer-aided content analysis and represented by the help of Wordle.net – the tool for generating “word clouds” from text that is provided. The outcome of this research is the content of teachers’ professional identity discussed and analysed in the light of various theories and in close link with the concepts of “professional career”, “personality development”, “career” and “self-concept”. Based on the keywords provided by teachers, the teacher’s professional identity structure consisting of 4 components: professional “self-concept”, harmony of professional identity, successful self-determination and creative professional activity was elaborated by adding criteria notions, as well as the content analyses of teachers’ narratives was used to identify professional identity development statuses.